Analisis α-Mangostin dalam Minuman Herbal Kulit Buah Manggis (Garcinia mangostana L.) dengan Metode Kromatografi Lapis Tipis-Densitometri - Regina Andayani; Friardi Ismed (Jurnal Sains Farmasi & Klinis, 2017)
Some herbal formulation containing α-mangostin as a marker compound in the pericarp of the mangosteen (Garcinia mangostana L.) are marketed now in Indonesia. The determination of the component of preparation both qualitatively and quantitatively is essential to ensure quality of the product. This research is aimed to develop a TLC (Thin Layer Chromatography)-densitometry method to analyze α-mangostin in the herbal drinks of mangosteen rind. The analysis was performed with TLC Scanner using Camag TLC Scanner 4 with Wincats software. Silica gel 60 F254 (Merck) plates (20x20 cm: 200 μm thickness) were used as stationary phase and mixture of chloroform and ethyl acetate (9:1,v/v) as a mobile phase. The developed chromatogram was scanned at 316 nm, the wavelength of maximum absorption for α-mangostin. At this condition, the Rf value of α-mangostin is 0.48. Regression analysis of the calibration data showed an excellent linear relationship between peak-area vs drug concentration. Linearity was found to be in the range of 50-400 µg/mL. The suitability of developed TLC densitometry method for estimation of α-mangostin was established by validating it as per the ICH guidelines. The limits of detection (LOD) and quantification (LOQ) for α-mangostin were found to be 54.38 μg/mL and 181.28 μg/mL. The developed method was found to be linear (r=0,99415), precise (RSD <1.28 % and < 2.39 % for intra-day and inter-day precision) and accurate (mean recovery of 90.04%). Results of the samples analysis showed that sample A does not contain α-mangostin, whereas sample B and C contain α-mangostin. The average concentrations obtained for samples B and C were 0.040% w/v and 0.118% w/v, respectively. The developed method has been successfully applied for the determination of α-mangostin in the herbal drinks of mangosteen rind.